Method for treating pulp waste water by using corallite-like MOG-Fe / Al flocculant

By using MOG-Fe/Al flocculant in the shape of coral stone, and using the composite structure of iron-aluminum mixture and phenylatic acid, the existing flocculant has solved the problem of low efficiency and poor settlement when treating slurry wastewater, and achieved the The efficient treatment of slurry wastewater has a turbidity removal rate of 98.3%.

CN119390208AActive Publication Date: 2025-02-07TARIM UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411625026.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-07
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

When treating slurry wastewater, existing flocculants have problems such as low flocculation efficiency, poor settlement and secondary pollution, making it difficult to effectively remove high turbidity and high organic matter in slurry wastewater.

Method used

The MOG-Fe/Al flocculant with coral stone-like shape is prepared by hydrothermal synthesis reaction, and the composite structure of iron-aluminum mixture and phenylatic acid is used to form a porous irregular morphology gel material to improve the stability of the flocculant and settlement performance.

Benefits of technology

The flocculation treatment efficiency of slurry wastewater is significantly improved, the turbidity removal rate can reach 98.3%, and the operating cost and energy consumption are reduced, providing an efficient wastewater treatment solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390208A_ABST
    Figure CN119390208A_ABST
Patent Text Reader

Abstract

The invention discloses a method for treating pulp waste water by using a corallite-like MOG-Fe / Al flocculating agent. The method comprises the following steps: preparing the MOG-Fe / Al flocculating agent by using aluminum nitrate, ferric nitrate and trimesic acid; the method comprises the following steps: diluting the cypress wastewater, adjusting the pH and temperature, adding a flocculating agent, and standing for settling. The MOG-Fe / Al flocculant is dense net-shaped colloidal particles which are provided with more holes and are similar to corallite in shape, has interwoven fibers or particles, is rich in mesoporous structure, can provide numerous active centers and is beneficial to diffusion of molecules in the holes, and meanwhile, the specific surface area of the material is large, so that the adsorption performance of the flocculant in water treatment is further improved; the removal rate is improved. Results show that when the addition amount of MOG-Fe / Al is 1.0 g, the concentration of the wastewater is diluted to 100 times, the pH is 9, the flocculation temperature is 30 DEG C, the flocculation time is 12 hours, and the turbidity removal rate of the wastewater can reach 98.3%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and more specifically to a method for treating pulp wastewater by using a coral-like MOG-Fe / Al flocculant. Background Art

[0002] Pulp wastewater mainly comes from the pulp and paper industry. It is wastewater generated during wood processing and pulp extraction. Its composition is complex, mainly including lignin, cellulose, various organic compounds and inorganic substances, and may also contain bleaching agents and other chemicals. As a major cotton-producing province in China, the Xinjiang Uygur Autonomous Region has a rapidly developing cotton textile industry, which produces a large amount of pulp wastewater every year. How to efficiently treat pulp wastewater containing a large amount of cotton linters, cellulose, wax, pectin, fat, sand and gravel and other impurities to meet the first-level emission standards formulated by the autonomous region is an important prerequisite for enterprises to face the common development of environmental protection and green production in the Xinjiang Uygur Autonomous Region, and it is also an effective way to achieve the recycling of water resources in the Xinjiang Uygur Autonomous Region.

[0003] At present, the treatment of pulp wastewater in Xinjiang Uygur Autonomous Region mainly adopts physical methods, chemical methods, biological methods, membrane separation technology and advanced oxidation technology. The physical method removes suspended matter and large particle pollutants through sedimentation, filtration and flotation; the chemical method removes soluble pollutants and harmful substances by adding chemical agents for coagulation-flotation and redox reaction. The biological method uses aerobic or anaerobic microorganisms to degrade organic matter and reduce organic load. Membrane separation technologies such as ultrafiltration, nanofiltration and reverse osmosis achieve deep treatment; advanced oxidation technology uses strong oxidants or photocatalysis to degrade difficult-to-degrade organic matter. In order to improve the utilization rate of pulp wastewater, realize the reuse of water resources, and solve the problems of high energy consumption, high treatment cost, low recovery efficiency and complex operation in the pulp wastewater treatment process, flocculation treatment has always been the most effective wastewater treatment method, and the development of efficient new flocculants has become the primary goal of researchers.

[0004] However, the existing flocculants used to treat wastewater include polyaluminium chloride (PAC), polyacrylamide (PAM), aluminium sulfate, etc. Due to the complex composition, high concentration of suspended solids and large content of organic matter in pulp and cypress wastewater, the single chemical structure and fixed flocculation mechanism structure of the existing flocculants lead to problems such as low flocculation efficiency, poor flocculation sedimentation and secondary pollution when used to treat pulp and cypress wastewater. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to improve the pore structure of the existing flocculant and improve its efficiency in treating pulp wastewater. To this end, the present invention provides a method for treating pulp wastewater using a coral-like MOG-Fe / Al flocculant.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The present invention provides a method for treating pulp wastewater by using a coral-like MOG-Fe / Al flocculant, comprising the following steps:

[0008] (1) Preparation of MOG-Fe / Al flocculant:

[0009] Aluminum nitrate, ferric nitrate and trimesic acid are mixed, ethanol is added, and the mixture is stirred and dissolved at room temperature; the mixture is then sealed for hydrothermal synthesis reaction, cooled to room temperature after the reaction, and freeze-dried to obtain the product;

[0010] (2) Dilute the pulp wastewater stock solution, let it stand, and then perform subsequent treatment on the diluted wastewater; adjust the pH and temperature of the diluted wastewater, add MOG-Fe / Al flocculant, let it stand and settle, and then the treatment is completed.

[0011] The present invention uses a mixture of iron and aluminum: iron and aluminum are commonly used flocculants and have good flocculation effects. 2+ or Fe 3+ ) has a strong coagulation ability in water and can effectively remove suspended matter and colloids in water, while aluminum ions (Al 3+ ) can form larger flocs and increase sedimentation. The combination of these two ions allows the flocculant to maintain excellent performance over a wide pH range. As an organic polymer material, trimesic acid helps to improve the stability and structural strength of the flocculant and can be adjusted for specific water quality conditions. The introduction of this material helps to increase the molecular weight of the flocculant, thereby improving its role in water treatment.

[0012] The structure of the MOG-Fe / Al flocculant prepared by the present invention is different from that of conventional flocculants based on single metal or other polymer materials. The composite structure of the MOG-Fe / Al of the present invention enables it to effectively form larger flocs and higher sedimentation rates during the reaction process, which is particularly important for the treatment of pulp wastewater with high turbidity and high organic matter content.

[0013] In addition, since pulp wastewater usually contains high concentrations of organic matter (such as lignin, cellulose) and complex colloidal particles, this requires the flocculant to not only react effectively with the organic matter, but also to be able to stably form larger sedimentation flocs. Based on the structural characteristics of the MOG-Fe / Al of the present invention, it shows a better treatment effect when removing these organic matter. If iron and aluminum are replaced by other metals, such as zinc, magnesium and other metals, although they also have certain chemical precipitation capabilities, their hydrolysis and ability to form flocs are inferior to iron and aluminum; if other organic polymer materials are used, such as polyaluminum chloride, polyacrylamide, polyvinyl alcohol, polypropylene alcohol and other materials, due to their relatively simple structures, the obtained flocculants will be insufficient in treatment effects.

[0014] Preferably, the pulp wastewater described in the present invention comes from the pulping and papermaking industry, and is black liquor produced during wood processing and pulp extraction, and is rich in humic acid, fulvic acid, lignin, cellulose and chemical additives.

[0015] Preferably, the UV of the pulp wastewater 600 ≥2, turbidity ≥35NTU, pH ≥11;

[0016] Among them, the composition of pulp wastewater is complex, mainly including lignin, cellulose, various organic compounds and inorganic substances, as well as bleaching agents and other chemicals. It usually has high biochemical oxygen demand (BOD), chemical oxygen demand (COD) and turbidity, and the water color is darker.

[0017] Preferably, in step (1), the molar ratio of aluminum nitrate, ferric nitrate and trimesic acid is 15:10:(16-17);

[0018] Preferably, in step (1), the mass ratio of trimesic acid to ethanol is (4-5) g:70 mL; the stirring time is 20-30 min;

[0019] Preferably, in step (1), the temperature of the hydrothermal synthesis reaction is 120-150° C. and the time is 1-3 h; the temperature of the freeze-drying is -60 to -65° C. and the time is 12-24 h;

[0020] Preferably, in step (2), the dilution multiple of the pulp wastewater stock solution is 50-550 times; and the standing time after dilution is 10-20 minutes;

[0021] More preferably, in step (2), the dilution factor of the pulp wastewater stock solution is 100 times;

[0022] Among them, if the dilution degree is less than 100 times, the pollutant concentration in the wastewater is too high, the flocculant is insufficient, and it reaches its limit; when the dilution exceeds 100 times, the pollutant concentration is too low, the flocculant is excessive, and some of them fail to play a role, but instead generate new pollutants, resulting in a decrease in removal rate;

[0023] Preferably, in step (2), the pH of the diluted wastewater is adjusted to 6-12 and the temperature is adjusted to 20-70°C;

[0024] More preferably, in step (2), the pH of the diluted wastewater is adjusted to 9 and the temperature is adjusted to 30°C;

[0025] Among them, the pH has a significant effect on the activity of the flocculant. The hydroxyl group on the surface of the flocculant plays a key role in the adsorption process. The stronger the alkalinity of the solution, the lower the degree of protonation. The most suitable pH adjustment for this method is 9. At the same time, heating at low temperature can enhance the activity of the flocculant and improve the flocculation effect. However, too high a temperature will reduce the activity of some flocculants, resulting in a decrease in the removal rate. The most suitable temperature for this method is 30°C.

[0026] Preferably, in step (2), the ratio of the mass of the added MOG-Fe / Al flocculant to the volume of the diluted wastewater is 5-15 g:1 L;

[0027] More preferably, in step (2), the ratio of the mass of the added MOG-Fe / Al flocculant to the volume of the diluted wastewater is 10 g:1 L;

[0028] If the amount of flocculant used is too large, the excessive amount of flocculant will lead to enhanced interactions between flocculants, forming large flocs, which may be difficult to settle or filter, thereby reducing the flocculation effect;

[0029] Preferably, in step (2), the time for static sedimentation after adding the MOG-Fe / Al flocculant is 1-12 hours;

[0030] More preferably, in step (2), the settling time after adding the MOG-Fe / Al flocculant is 12 hours.

[0031] The technical solution of the present invention achieves the following beneficial technical effects:

[0032] Since pulp wastewater has the characteristics of high turbidity and concentration, general flocculants have poor flocculation effect, slow sedimentation rate or limited removal effect on specific pollutants when used for treatment because most general flocculants are based on cationic or anionic polymer structures. The present invention uses aluminum and iron as metal ions, trimesic acid as a ligand, and ethanol as a reaction solvent. A hydrothermal reaction is carried out at a temperature of 120-150°C to synthesize a functional coral-like metal-organic gel composite material MOG-Fe / Al flocculant for treating pulp wastewater, and the treatment effect of pulp wastewater is evaluated and the process conditions are optimized. Among them, the MOG-Fe / Al material synthesized by the present invention has a porous and irregular morphology, and its specific surface area is 360.5m 2 / g, belonging to micro-mesoporous materials, the MOG-Fe / Al gel material has shown important practical value and broad development prospects in the field of pulp wastewater treatment. The specific analysis is as follows:

[0033] The MOG-Fe / Al flocculant prepared by the present invention is a densely meshed colloidal particle with many holes and similar to the shape of coral stone, with fibers or particles interwoven with each other. The average pore size of MOG-Fe / Al is concentrated at 1.7nm, 2.4nm and 5.0nm, which belongs to a micro-mesoporous material, and the mesoporous structure is rich. These structures not only provide a large number of active centers for the application of the material, but also facilitate the diffusion of the target molecules in the pores. The presence of pores in the MOG-Fe / Al flocculant helps to expand the specific surface area of ​​the material, thereby improving its adsorption performance in water treatment. At the same time, the density and anisotropy of the surface network of the material are related to its physical and chemical properties.

[0034] The present invention uses MOG-Fe / Al flocculant to treat pulp wastewater, and optimizes the process conditions for treating wastewater. The results show that when the MOG-Fe / Al dosage is 1.0g, the wastewater concentration is diluted to 100 times, the pH is 9, the flocculation temperature is 30°C, and the flocculation time is 12h, the wastewater turbidity removal rate can reach 98.3%, and the flocculation treatment effect on pulp wastewater is the best. MOG-Fe / Al shows excellent flocculation performance in cotton spinning wastewater treatment and has great application potential. It provides a feasible new solution for cotton textile industry wastewater treatment in Xinjiang Uygur Autonomous Region, provides new ideas for cotton pulp wastewater treatment, and is of great significance to the sustainable development of water resources protection and ecological environment in Xinjiang Uygur Autonomous Region, especially in southern Xinjiang. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The absorbance of wastewater at different wavelengths in Example 3 of the present invention;

[0036] Figure 2Turbidity removal rate of different MOG-Fe / Al flocculant dosages in Example 3 of the present invention;

[0037] Figure 3 Turbidity removal rate of MOG-Fe / Al flocculant for wastewater of different concentrations in Example 4 of the present invention;

[0038] Figure 4 Turbidity removal rate of wastewater at different temperatures by MOG-Fe / Al flocculant in Example 5 of the present invention;

[0039] Figure 5 Turbidity removal rate of MOG-Fe / Al flocculant for wastewater with different pH values ​​in Example 6 of the present invention;

[0040] Figure 6 Turbidity removal rate of MOG-Fe / Al flocculant at different standing times in Example 7 of the present invention;

[0041] Figure 7 SEM images of MOG-Fe / Al, MOG-Fe and MOG-Al in the present invention;

[0042] Among them, a: MOG-Fe / Al (500nm); b: MOG-Fe (500nm); c: MOG-Al (500nm); d: MOG-Fe / Al (1μm); e: MOG-Fe (1μm); f: MOG-Al (1μm);

[0043] Figure 8 FT-IR images of MOG-Fe / Al, MOG-Fe and MOG-Al in the present invention;

[0044] Fig. 9 XRD patterns of MOG-Fe / Al, MOG-Fe and MOG-Al in the present invention;

[0045] Fig.10 TG diagrams of MOG-Fe / Al, MOG-Fe and MOG-Al in the present invention;

[0046] Fig.11 X-ray photoelectron spectroscopy analysis of MOG-Fe / Al in Example 1 of the present invention;

[0047] Fig.12 N2 adsorption-desorption test diagram of MOG-Fe / Al in Example 1 of the present invention;

[0048] Fig.13 Pore ​​size distribution diagram of MOG-Fe / Al in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical scheme and technical effect of the invention of this application clearer, the technical scheme in the embodiment of this application will be clearly and completely described below in conjunction with the drawings in the embodiment of this application. Obviously, the described embodiment is a part of the embodiment of this application, not all the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0050] The following is a detailed description of a method for treating pulp wastewater using a coral-like MOG-Fe / Al flocculant according to the present invention through specific embodiments.

[0051] The pulp wastewater (black liquor) used in the following examples is taken from Alaer Zhongtai Textile Technology Co., Ltd.; sample specifications: black liquor concentration 50% (i.e., the mass percentage of solids in black liquor). Sample characteristics: black, paste-like, with a light grassy smell. Water solubility: easily soluble; viscosity: 41040mpa·s; humic acid mass concentration in black liquor: 5.12%, fulvic acid mass concentration: 20.04%, other organic matter mass concentration: 59.36%; water mass concentration: 10.11%; pH value: 12.00; black liquor nutrients: N: 0.280%; P: 0.598%; K: 1.520%; total nutrient mass percentage: 2.398%.

[0052] Example 1 Preparation of MOG-Fe / Al flocculant

[0053] 5.625 g of aluminum nitrate nonahydrate (15 mmol), 4.04 g of ferric nitrate nonahydrate (10 mmol), and 4.625 g of trimesic acid (16.667 mmol) were weighed in turn and placed in a 500 mL beaker, and then 70 mL of ethanol was added and stirred at room temperature for 20 min to dissolve. The solution was then placed in a hydrothermal synthesis kettle and sealed, placed in an oven at 120 ° C to react for 2 h, and the sample was taken out after cooling to room temperature, and then dried in a freeze dryer at -64.3 ° C for 12 h to obtain MOG-Fe / Al material.

[0054] Comparative Example 1 Preparation of MOG-Fe flocculant

[0055] 4.04 g of ferric nitrate nonahydrate (10 mmol) and 4.625 g of trimesic acid (16.667 mmol) were weighed in turn and placed in a 500 mL beaker, and then 70 mL of ethanol was added and stirred for 20 min at room temperature to dissolve. The solution was then placed in a hydrothermal synthesis kettle and sealed, placed in an oven at 120 ° C to react for 2 h, and the sample was taken out after cooling to room temperature, and then dried in a freeze dryer at -64.3 ° C for 12 h to obtain MOG-Fe material.

[0056] Comparative Example 2 Preparation of MOG-Al flocculant

[0057] 5.625 g of aluminum nitrate nonahydrate (15 mmol) and 4.625 g of trimesic acid (16.667 mmol) were weighed in turn and placed in a 500 mL beaker, and then 70 mL of ethanol was added and stirred for 20 min at room temperature to dissolve. The solution was then placed in a hydrothermal synthesis kettle and sealed, placed in an oven at 120 ° C to react for 2 h, and the sample was taken out after cooling to room temperature, and then dried in a freeze dryer at -64.3 ° C for 12 h to obtain MOG-Al material.

[0058] Example 2 Method for treating pulp wastewater using coral-like MOG-Fe / Al flocculant

[0059] Distilled water was added to dilute the pulp wastewater stock solution 100 times. After standing for 10 minutes, the pH of the diluted wastewater was adjusted to 9. At 30°C, the MOG-Fe / Al flocculant obtained in Example 1 was added (the mass ratio of the MOG-Fe / Al flocculant to the volume of the diluted wastewater was 10g:1L), and the solution was allowed to stand for 12 hours to complete the flocculation treatment.

[0060] The absorbance (measured after filtration) and turbidity (measured directly without filtration) of the pulp wastewater before and after treatment were measured using a UV-visible spectrophotometer and a turbidity meter. The change in absorbance can reflect the change in the concentration of certain solutes (such as organic matter) in the wastewater; the turbidity measurement can be used to evaluate the scattering ability of suspended matter in the water to light, and then evaluate the treatment effect of the flocculant on the wastewater.

[0061] Among them, the determination of the maximum absorption wavelength: the absorbance of the diluted wastewater at wavelengths of 550nm, 560nm, 570nm, 580nm, 590nm, 600nm, 610nm, 620nm, 630nm, 640nm, and 650nm is measured respectively. The absorbance of the wastewater at different wavelengths is as follows: Figure 1 As shown in the figure, the maximum absorption wavelength is finally determined to be 600nm, so the experimental measurement is carried out at this wavelength.

[0062] The experimental results show that the treatment of pre-slurry wastewater: UV 600 : 2.1, turbidity: 35+1.5NTU, pH: 12.00±0.01;

[0063] Treatment of post-pulping wastewater: UV 600 : 0.079, turbidity: 0.59NTU, pH: 6.00;

[0064] Example 3 Flocculation effect of different MOG-Fe / Al flocculant dosages

[0065] Take 1mL of pulp cypress wastewater stock solution, add distilled water to dilute it 120 times, let it stand for 10 minutes, adjust the pH of the diluted wastewater to 10, and add 0.5-1.5g MOG-Fe / Al flocculant (that is, the mass ratio of MOG-Fe / Al flocculant to the volume of diluted wastewater is 5-15g:1L) in a constant temperature water bath at 20℃, and let it stand for 1 hour to complete the flocculation treatment.

[0066] In this example, the mass ratio of MOG-Fe / Al flocculant to the volume of diluted wastewater was changed to study the flocculation effect of different MOG-Fe / Al flocculant dosages, measure the turbidity value of wastewater before and after flocculation, and calculate the turbidity removal rate to evaluate the flocculation effect. The results are shown in Table 1. Figure 2 shown.

[0067] Turbidity removal rate = (turbidity value before flocculation - turbidity value after flocculation) / turbidity value before flocculation × 100%

[0068] Table 1 Flocculation effect of different MOG-Fe / Al flocculant dosages

[0069] MOG-Fe / Al dosage / g 0.5 0.62 0.75 0.79 0.88 1 Turbidity removal rate / % 69 72.2 76.8 79 84.5 88 MOG-Fe / Al dosage / g 1.1 1.2 1.3 1.38 1.5 Turbidity removal rate / % 85 82 80.9 78 76.5

[0070] According to Table 1, Figure 2 It can be seen that between 0.5-1.0g, as the dosage increases, the turbidity removal rate gradually increases. Between 1.0-1.5g, as the dosage increases, the removal rate gradually decreases, and the optimal dosage is 1.0g. This may be because as the amount of flocculant increases, too much flocculant will lead to enhanced interactions between flocculants, forming large floccules, which may be difficult to settle or filter, thereby reducing the flocculation effect; flocculants may cause the pH value of the solution to change, affecting the performance of the flocculant, and thus affecting the flocculation effect; when the optimal dosage is reached, continuing to increase the amount of flocculant will not cause flocculation but will dissolve in the wastewater to become a new pollutant. In addition, the flocculant itself in the experiment is also colored, and excessive addition will cause new pollution to the wastewater.

[0071] Example 4 Flocculation effect of MOG-Fe / Al on wastewater of different concentrations

[0072] Take 1mL of pulp cypress wastewater stock solution, add distilled water to dilute it 50-550 times respectively, let it stand for 10 minutes, adjust the pH of the diluted wastewater to 10, add 1.0g MOG-Fe / Al flocculant in a constant temperature water bath at 20℃, and let it stand for 1 hour to complete the flocculation treatment.

[0073] In this example, the dilution multiple of the pulp wastewater stock solution with distilled water was changed to study the flocculation effect of MOG-Fe / Al on wastewater of different concentrations, measure the turbidity value of the wastewater before and after flocculation, and calculate the turbidity removal rate to evaluate the flocculation effect. The results are shown in Table 2. Figure 3 shown.

[0074] Table 2 Flocculation effect of MOG-Fe / Al gel material on wastewater of different concentrations

[0075] Wastewater dilution multiple 50 100 150 200 250 300 Turbidity removal rate / % 60.4 92.6 89.8 85.4 80.3 74.3 Wastewater dilution multiple 350 400 450 500 550 Turbidity removal rate / % 69.2 67.3 61.2 56.2 45.8

[0076] According to Table 2, Figure 3 When 1.0g flocculant is added to the wastewater when it is diluted 50 times, the turbidity removal rate is only 60.3%; when it is diluted 100 times, the removal rate increases to 92.5%. As the dilution increases, the removal rate gradually decreases. The reason is that when the dilution is less than 100 times, the pollutant concentration in the wastewater is too high, the flocculant is insufficient, and it reaches its limit; when the dilution exceeds 100 times, the pollutant concentration is too low, the flocculant is excessive, and some of them fail to play a role, but instead generate new pollutants, resulting in an increase in turbidity values. This shows that the optimal treatment concentration is a 100-fold dilution.

[0077] Example 5 Flocculation effect of MOG-Fe / Al on wastewater at different temperatures

[0078] Take 1mL of pulp cypress wastewater stock solution, add distilled water to dilute it 100 times, let it stand for 10 minutes, adjust the pH of the diluted wastewater to 10, add 1.0g MOG-Fe / Al flocculant under constant temperature water bath conditions at different temperatures (20-70℃), and let it stand for 1 hour to complete the flocculation treatment.

[0079] In this example, the temperature conditions of the flocculation treatment were changed to study the flocculation effect of MOG-Fe / Al at different temperatures, the turbidity value of the wastewater before and after flocculation was measured, and the turbidity removal rate was calculated to evaluate the flocculation effect. The results are shown in Table 3. Figure 4 shown.

[0080] Table 3 Flocculation effect of MOG-Fe / Al on wastewater at different temperatures

[0081] Temperature / ℃ 20 25 30 35 40 45 Turbidity removal rate / % 92.5 94.4 96.4 95.3 94.2 91.3 Temperature / ℃ 50 55 60 65 70 Turbidity removal rate / % 86.3 86.1 85.8 85.2 85.1

[0082] According to Table 3, Figure 4, the wastewater removal rate of MOG-Fe / Al flocculant gradually increased at 20℃ to 30℃, but began to decrease after exceeding 30℃. When it reached 50℃, the turbidity value did not change significantly, indicating that the effect of temperature on the flocculant was limited. At low temperatures, heating enhanced the activity and improved the flocculation effect. However, at too high temperatures, part of the activity decreased, resulting in a decrease in turbidity removal rate; subsequently, the activity stabilized and the turbidity removal rate remained above 80%. At 30℃, the removal rate reached 96.4%, indicating that the optimal operating temperature was 30℃.

[0083] Example 6 Flocculation effect of MOG-Fe / Al on wastewater with different pH values

[0084] Take 1mL of pulp cypress wastewater stock solution, add distilled water to dilute it 100 times, let it stand for 10 minutes, adjust the pH of the diluted wastewater to 1-12, add 1.0g MOG-Fe / Al flocculant in a constant temperature water bath at 30℃, and let it stand for 1 hour to complete the flocculation treatment.

[0085] In this example, the pH conditions of the wastewater during flocculation treatment were changed to study the flocculation effect of MOG-Fe / Al on wastewater with different pH values, measure the turbidity value of the wastewater before and after flocculation, and calculate the turbidity removal rate to evaluate the flocculation effect. The results are shown in Table 4. Figure 5 shown.

[0086] Table 4 Flocculation effect of MOG-Fe / Al on wastewater with different pH values

[0087] pH 12 11 10 9 8 7 Turbidity removal rate / % 92.8 94.6 96.8 97.2 97.1 95.3 pH 6 5 4 3 2 1 Turbidity removal rate / % 90.2 84.4 78.4 74.3 72.2 69.6

[0088] According to Table 4, Figure 5 It can be seen that the MOG-Fe / Al gel flocculant exhibits different flocculation effects in wastewater with different pH values. As the pH value increases, the turbidity removal rate gradually increases, but begins to decrease after exceeding 9, indicating that the pH has a significant effect on its activity. In the pH range of 7 to 10.5, the turbidity removal rate is high, which may be because the hydroxyl groups on the surface of the adsorbent play a key role in the adsorption process. Extreme pH values ​​will affect the flocculation effect. The stronger the alkalinity of the solution, the lower the degree of protonation. This is because the alkaline solution contains more hydroxide ions (OH-), which leads to the protonation of hydrogen ions (H + ) increases, thereby reducing the concentration of free hydrogen ions in the solution. Therefore, as the alkalinity increases, the acidity (pH value) of the solution increases and the degree of protonation decreases accordingly. Therefore, when using MOG-Fe / Al gel to treat wastewater, the optimal pH adjustment should be 9.

[0089] Example 7 Flocculation effect of different standing times on MOG-Fe / Al

[0090] Take 1mL of pulp cypress wastewater stock solution, add distilled water to dilute 100 times, let it stand for 10 minutes, adjust the pH of the diluted wastewater to 9, add 1.0g MOG-Fe / Al flocculant in a constant temperature water bath at 30℃, let it stand for sedimentation and flocculation treatment for 1-12 hours, and the treatment is completed.

[0091] In this example, the flocculation effect of MOG-Fe / Al was studied by changing the standing time of the flocculation treatment, measuring the turbidity value of the wastewater before and after flocculation, and calculating the turbidity removal rate to evaluate the flocculation effect. The results are shown in Table 5. Figure 6 shown.

[0092] Table 5 Flocculation effect of MOG-Fe / Al at different standing times

[0093] Standing time / h 1 2 3 4 5 6 Turbidity removal rate / % 97.4 97.5 97.6 97.7 97.9 97.9 Standing time / h 7 8 9 10 11 12 Turbidity removal rate / % 98.1 98.2 98.2 98.3 98.3 98.3

[0094] According to Table 5, Figure 6 It can be seen that with the increase of standing time, the turbidity removal rate of MOG-Fe / Al gel for wastewater continues to increase, indicating that the longer the standing time, the better the flocculation effect. It is recommended to select 12h as the optimal treatment time.

[0095] Performance measurement and analysis

[0096] The properties of MOG-Fe / Al, MOG-Fe and MOG-Al materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were measured and analyzed, and the results are as follows.

[0097] (1) Scanning electron microscopy (SEM)

[0098] Figure 7 The SEM images of MOG-Fe / Al, MOG-Fe and MOG-Al are shown in Figure 2. Figure 7 It can be seen from Figures 7a, 7b, and 7c that MOG-Fe / Al is a dense network of colloidal particles with many holes and similar to the shape of coral stone, showing interwoven fibers or particles. The size and distribution of the holes may vary depending on the composition of the gel and the drying conditions. The presence of pores helps to expand the specific surface area of ​​the material, thereby improving its adsorption performance in water treatment. The density and anisotropy of the network on the surface of the material may affect its physical and chemical properties. The surfaces of MOG-Al and MOG-Fe are irregular morphologies with dense protrusions. The surface of the material does not dry like MOG-Fe / Al to produce a large number of network structures. Figure 7d, 7e, 7f, it can be seen that the morphology of MOG-Fe / Al obtained by 1μm scanning shows many rod-shaped attached particles, the surface of MOG-Fe is similar to volcanic pumice with a small amount of particles attached, and the surface of MOG-Al is attached with a large number of irregular particles. The shape, size and distribution of these particles or fibers are also related to the raw materials and preparation process. Through observation, the surface of the dried gel may show different degrees of roughness.

[0099] (2) Fourier transform infrared spectroscopy (FT-IR)

[0100] Figure 8 The FT-IR images of MOG-Fe / Al, MOG-Fe and MOG-Al show that all materials have a -1 The stretching vibration peak of the hydroxyl group of the adsorbed water appeared at 2538 cm -1 The CH stretching vibration peak of the benzene ring of the organic ligand appears at 1663 cm -1 The CC stretching vibration peak of the aromatic ring in the organic ligand appears at 1384 cm -1 The symmetrical stretching vibration peak of BTC carboxyl C=O appeared at 1390 cm -1 The strongest band at cm is due to the asymmetric stretching vibration of the carboxylic acid group. The peak of the CH disubstituted para substitution of the benzene ring in the fingerprint region appears at 810 cm -1 At 678cm -1 and 667cm -1 CN fatty alcohols appear in two places.

[0101] (3) X-ray diffraction (XRD)

[0102] XRD patterns of MOG-Fe / Al, MOG-Fe and MOG-Al, such as Fig. 9As shown. The diffraction peaks of MOG-Fe / Al in the figure are strong, but there are broad peaks, which may be due to the amorphous state or low crystallinity. The presence of more impurity peaks in MOG-Fe and MOG-Al further proves that their purity is not high. The relevant peaks of these two MOGs are closely matched, confirming that the crystal structure of the material remains intact after the change. The wide plate diffraction peaks of 22°-25° prove that the crystallinity of these three samples is poor. There is no long-range order in the structure, indicating that the amorphous structure of the three samples may be more prone to fracture or deformation and have poor thermal stability, affecting the reliability of high-temperature applications. In addition, by analyzing the matching degree of the diffraction peaks of the three MOG materials, it is found that after adding aluminum nitrate nonahydrate and iron nitrate nonahydrate for modification, the samples show obvious differences in broad peaks, indicating that the crystal structure has changed. The diffraction peak PDF card numbers of the materials are 70-1103 and 70-2161, and when the incident angle of the X-ray beam relative to the surface is 70°, the relative enhancement of the (203) peak indicates that the MOG material has a plane-preferred orientation.

[0103] (4) Thermogravimetry (TG)

[0104] TG diagrams of MOG-Fe / Al, MOG-Fe and MOG-Al, such as Fig.10 As shown. At 0-177°C, the sample was observed to have a significant mass loss of 14.1% to 22.5%, which is usually related to the evaporation of water or the release of low-volatile components. At this stage, water or solvent is released from the gel network. Between 177 and 322°C, the sample was observed to have a significant mass loss of 17.4% to 8.3%. This stage may be related to the loss of organic ligands, polymer degradation or phase change. At a temperature of 322-503°C, the mass loss was 13.4% to 34.6%, and MOG-Fe had the largest loss, which can be attributed to the removal of residual solvents and the decomposition of the porous gel matrix. At this stage, the decomposition of the molecular skeleton and the loss of remaining organic ligands may lead to some collapse of the MOG skeleton. The residues may involve carbon and iron oxides, etc., which can be attributed to the removal of residual solvents and the decomposition of the porous gel matrix. After exceeding 503°C, the mass of the sample tends to be stable, and the final residual mass is 29% to 39%. This residual mass can be used to infer the content of inorganic components or carbonization products of the material. (5) X-ray photoelectron spectroscopy (XPS)

[0105] To further analyze the chemical bond information of MOG-Fe / Al, the material was characterized by XPS. Fig.11 The binding energy (BEs) peaks are 75.16, 285.21, 407.19, 532.12, and 711.53 eV, indicating the presence of Al, C, N, O, and Fe elements on the sample surface ( Fig.11 a) C 1sPeak fitting shows that the peaks at 284.80 and 289.09 eV correspond to the C—C / C=C and O—C=O bonds of the carboxyl group, respectively. Fig.11 b) Fe 2p High-resolution XPS spectra show that Fe 2+ and Fe 3+ The characteristic peaks of 709.21 and 711.83 eV are attributed to Fe 2+ 2p1 / 2 and Fe 3+ 2p2 / 3 The spin-orbit splitting of Fe 2+ 2p The satellite peak is located at 715.01eVFe 3+ 2p2 / 3 The satellite peak at 729.36 eV confirms the Fe 3+ Alignment with BTC. 2p The BEs peaks are 72.56 eV and 75.26 eV, corresponding to metallic Al and adsorbed alumina, respectively, further confirming the presence of Al element ( Fig.11 d) Both MOG-Fe / Al and MOG-FeAl spectra show N-O bonds. MOG-FeAl N 1s The BEs peaks are 396.60, 399.31, 400.88, 404.16 and 407.29 eV, corresponding to metal nitride, pyrrolic nitrogen and nitrogen oxide, respectively. 1s The fitting curves of the peaks are at 529.29 and 532.10 eV, corresponding to the metal O and CO bonds, respectively ( Fig.11 f).

[0106] (6) Specific surface area detection (BET)

[0107] To determine the pore size distribution and specific surface area of ​​MOG-Fe / Al, N2 adsorption-desorption tests were performed (see Fig.12 ). MOG-Fe / Al presents a type IV adsorption isotherm, and there is a hysteresis loop between the adsorption and desorption branches, which means that the sample has mesoporous properties. At a relative pressure of P / P0=0.4-0.8, there is an obvious hysteresis loop between the adsorption branch and the desorption branch, indicating that the product has a high mesoporosity. Due to the characteristics of the H2(a) type hysteresis loop, it is not possible to rely solely on the desorption curve, so the adsorption curve was used for analysis. Based on the adsorption data, the BET surface area was calculated to be 360.532m 2 / g, the larger surface area gives MOG microcubes abundant surface active sites, promoting the reaction between molecules and sensing materials. Fig.13It shows that the average pore size of MOG-Fe / Al is concentrated at 1.7nm, 2.4nm and 5.0nm, which is a micro-mesoporous material with rich mesoporous structure. These structures not only provide numerous active centers for the application of the material, but also facilitate the diffusion of target molecules in the pores.

[0108] In summary, the present invention successfully synthesized the metal-organic gel (MOG) material MOG-Fe / Al, studied the flocculation treatment effect of the material in pulp wastewater, optimized the process conditions, and performed performance characterization analysis on the properties and structure of the synthesized material. The results show that when the MOG-Fe / Al dosage is 1.0g, the wastewater concentration is diluted to 100 times, the pH is 9, the flocculation temperature is 30°C, and the flocculation time is 12h, the wastewater turbidity removal rate can reach 98.3%, which is related to the differences in pore size, number of channels, gel properties of aluminum and iron, and internal structure. The characterization results show that the surface of the material is rough and the mesh distribution is dense. The MOG-Fe / Al obtained by the present invention exhibits excellent flocculation performance in the treatment of cotton spinning wastewater and has great application potential. The present invention prepares a new high-efficiency flocculation treatment agent MOG-Fe / Al for cotton spinning wastewater, which provides a feasible new solution for the treatment of cotton textile industry wastewater in Xinjiang Uygur Autonomous Region and provides a new idea for the treatment of cotton pulp wastewater.

[0109] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A method for treating pulp wastewater using a coral-like MOG-Fe / Al flocculant, characterized in that: The following steps are involved: (1) Preparation of MOG-Fe / Al flocculant: Aluminum nitrate, ferric nitrate and trimesic acid are mixed, ethanol is added, and the mixture is stirred and dissolved at room temperature; the mixture is then sealed for hydrothermal synthesis reaction, cooled to room temperature after the reaction, and freeze-dried to obtain the product; (2) Dilute the pulp wastewater and let it stand; adjust the pH and temperature of the diluted wastewater, add MOG-Fe / Al flocculant, let it stand and settle, and then the treatment is completed.

2. The method according to claim 1, characterized in that In step (1), the molar ratio of aluminum nitrate, ferric nitrate and trimesic acid is 15:10:(16-17); the mass ratio of trimesic acid to ethanol is (4-5) g:70 mL; and the stirring time is 20-30 min.

3. The method according to claim 1, characterized in that In step (1), the temperature of the hydrothermal synthesis reaction is 120-150° C. and the time is 1-3 h; the temperature of the freeze-drying is -60 to -65° C. and the time is 12-24 h.

4. The method according to claim 1, characterized in that In step (2), the pulp wastewater comes from the pulp and paper industry and is black liquor produced during wood processing and pulp extraction; the UV 600 ≥2, turbidity ≥35NTU, pH ≥11.

5. The method according to claim 1, characterized in that In step (2), the dilution ratio of the pulp wastewater is 50-550 times; and the standing time after dilution is 10-20 minutes.

6. The method according to claim 5, characterized in that In step (2), the dilution ratio of the pulp wastewater is 100 times.

7. The method according to claim 1, characterized in that In step (2), the pH of the diluted pulp wastewater is adjusted to 6-12 and the temperature is adjusted to 20-70°C.

8. The method according to claim 7, characterized in that In step (2), the pH of the diluted pulp wastewater is adjusted to 9 and the temperature is adjusted to 30°C.

9. The method according to claim 1, characterized in that In step (2), the mass ratio of the added MOG-Fe / Al flocculant to the volume of the diluted pulp wastewater is 5-15g:1L; and the static sedimentation time after adding the MOG-Fe / Al flocculant is 1-12h.

10. The method according to claim 9, characterized in that In step (2), the ratio of the mass of the added MOG-Fe / Al flocculant to the volume of the diluted pulp wastewater is 10g:1L; and the static sedimentation time after adding the MOG-Fe / Al flocculant is 12h.

Citation Information

Patent Citations

  • Magnetic metal organogel loaded silver phosphate composite photocatalyst, and preparation method and applications thereof

    CN109174198A

  • Atomic dispersion noble metal catalyst as well as preparation method and application thereof

    CN118698560A

  • Metal-organic gels and metal-organic aerogels fabricated from coordination polymer nanofibers

    JP2019521198A

  • Magnetic nanoparticles functionalized with cathecol, production and use thereof

    US20160331850A1